Epilepsy detection and monitoring - Shahid, A. (CRC Press, 2014)
Epilepsy is a chronic condition that is characterized by recurrent and unprovoked seizures. A seizure can be defined clinically as âintermittent paroxysmal, stereotyped disturbance of consciousness, behavior, emotion, motor function, perception, or sensation, which may occur singly or in combination and is thought to be the result of abnormal cortical neuronal discharges.â The exact type of seizure will depend on where it starts and then spreads within the brain. Abnormalities in synaptic transmission, neuronal excitability, voltage gated ion channels, neuronal proteins, and gene expression are all implicated in the pathogenesis of epilepsy. Â© 2015 by Taylor & Francis Group, LLC.